Pengaruh Penggunaan Teknologi Informasi terhadap Peningkatan Kinerja Guru - Sopiyah, Maria; Niswah, Choirun; Ibrahim, Ibrahim; Febriyanti, Febriyanti; Zulkipli, Zulkipli; Fatmawaty, Fatmawaty (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the impact of information technology usage on improving teacher performance at SMP Negeri 26 Palembang. The use of information technology is expected to enhance the efficiency and effectiveness of the teaching process, particularly in planning, implementation, evaluation, and improvement of educational programs. The research method employed is a quantitative approach, with data collection techniques including observations, questionnaires, and documentation. The subjects of this research are teachers at SMP Negeri 26 Palembang. Data analysis was conducted using simple linear regression tests and prerequisite tests to ensure the validity and reliability of the collected data. The research findings indicate that the use of information technology has a positive effect on enhancing teacher performance at SMP Negeri 26 Palembang. The regression coefficient of 0.606 suggests that every increase in the use of information technology can improve teacher performance. The t-test results show a value of t_calculated = 7.386 and t_table = 1.676 with a significance level of 0.000, indicating a significant effect. The determination test shows that information technology accounts for 52.2% of the improvement in teacher performance, while the remaining percentage is influenced by other factors. In conclusion, optimizing the use of information technology has a positive impact on teacher performance, and it is recommended that schools continue to support training and development of technology skills for teachers in the future